2017
DOI: 10.1111/bjd.15292
|View full text |Cite
|
Sign up to set email alerts
|

Facing the dilemma of patient-centred psoriasis care: a qualitative study identifying patient needs in dermatological outpatient clinics

Abstract: Consultations with a standardized structure do not match the individual challenges and healthcare needs of patients with psoriasis. In order to achieve a more patient-centred approach, health professionals should implement minor structural changes to dermatological services to meet patients' current needs and invite dialogue about the patients' emotional well-being and concerns that go beyond biomedical factors, as well as offer individualized health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 36 publications
(71 reference statements)
9
47
1
1
Order By: Relevance
“…Combined, the themes represent a conceptual model for understanding HRQoL in 12–17‐year‐old adolescents with psoriasis, reflecting a range of physical, psychological and social concerns. While previous qualitative studies have touched upon several of the identified issues in adult and paediatric psoriasis, our study goes further by providing an integrated conceptual model of HRQoL, which is specific to both psoriasis and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, the themes represent a conceptual model for understanding HRQoL in 12–17‐year‐old adolescents with psoriasis, reflecting a range of physical, psychological and social concerns. While previous qualitative studies have touched upon several of the identified issues in adult and paediatric psoriasis, our study goes further by providing an integrated conceptual model of HRQoL, which is specific to both psoriasis and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Struggling with unrecognized distress. Patients felt un supported and sometimes angry due to the perceived lack of medical attention or understanding among their family and com munity about psychological symptoms: "I was about to break down mentally…I wrote it on the questionnaire…but none of the physicians or nurses asked me about it" (26).…”
Section: Synthesismentioning
confidence: 99%
“…The participants in this study perceived a lack of personalized care and education, and believed it was made worse by standardized consultations in the dermatology outpatient setting. They also found routine follow‐ups to be burdensome.…”
mentioning
confidence: 91%
“…In this issue of the BJD , Khoury and colleagues present their qualitative study of the experiences and expectations of people with psoriasis who were receiving care at a hospital outpatient clinic after treatment from a private dermatologist had failed. From the patients’ perspectives, the clinic routines and consultations were often physician‐centred, and their individual contexts and questions were not considered adequately within often brief consultations.…”
mentioning
confidence: 99%
See 1 more Smart Citation